2020
DOI: 10.3389/fpsyg.2020.01743
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Virtual Reality Alone Does Not Promote Training Performance (but Sense of Presence Does)

Abstract: Virtual reality (VR) offers novel ways to develop skills and learning. This technology can be used to enhance the way we educate and train professionals by possibly being more effective, cost-efficient, and reducing training-related risks. However, the potential benefits from virtual training assume that the trained skills can be transferred to the real world. Nevertheless, in the current published scientific literature, there is limited empirical evidence that links VR use to better learning. The present inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

4
6

Authors

Journals

citations
Cited by 142 publications
(82 citation statements)
references
References 41 publications
1
78
2
1
Order By: Relevance
“…Females were also found to be more sensitive to emotional information in the simulated environment (Mousas et al, 2018 ), and to report a higher level of sense of embodiment (Scheibler and Rodrigues, 2018 ), as well as of presence, when 3D images were showed (Narciso et al, 2019 ). It has been often proposed that sense of presence and performance are often connected (e.g., Lombard and Ditton, 1997 ; Witmer and Singer, 1998 ; Grassini et al, 2020 ). The fact that females perform better may be due to the higher sense of presence (or a presence-related phenomenon such as realism) that female participants sometimes experience (see Bracken, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Females were also found to be more sensitive to emotional information in the simulated environment (Mousas et al, 2018 ), and to report a higher level of sense of embodiment (Scheibler and Rodrigues, 2018 ), as well as of presence, when 3D images were showed (Narciso et al, 2019 ). It has been often proposed that sense of presence and performance are often connected (e.g., Lombard and Ditton, 1997 ; Witmer and Singer, 1998 ; Grassini et al, 2020 ). The fact that females perform better may be due to the higher sense of presence (or a presence-related phenomenon such as realism) that female participants sometimes experience (see Bracken, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this information can be used to determine which sample of employees may be less susceptible to the use of these new visualization technologies. HMD-mediated VR environments are now often proposed to employees as training methods for safety procedures (for example, [115,116]) and has been proposed as a method to train specific tasks [117,118]. Thus, this kind of assessment will likely become increasingly important.…”
Section: Practical Implications Of the Present Studymentioning
confidence: 99%
“…These results indicate that the arm-reaching task in VEs may not facilitate sequential learning because of the lack of tactile stimulation. Furthermore, several studies have reported that motor learning in VEs is in uenced by individual factors 15,33,34 . For instance, experience with video games showed a positive impact on performance in VEs 15,35 .…”
Section: Discussionmentioning
confidence: 99%